2017
DOI: 10.3390/atmos8120239
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and Size Distribution of Culturable Bacteria in Ambient Air during Spring and Winter in Gliwice: A Typical Urban Area

Abstract: Abstract:The concentrations and size distributions of culturable bacterial aerosols were measured during spring and winter in outdoor air in Gliwice, Upper Silesia, Poland. This research on culturable bacteria was carried over a period of two years. The samples were collected using a six-stage Andersen cascade impactor (with aerodynamic cut-off diameters of 7.0, 4.7, 3.3, 2.1, 1.1, and 0.65 µm). The results showed that the average concentration of culturable bacterial aerosol was 355 CFU m −3 in spring, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 44 publications
6
29
1
4
Order By: Relevance
“…The most significant environmental factor influencing the viability of microorganisms is temperature. Higher temperature could promote the growth of fungi [41,42]. This is confirmed by the higher concentration levels of fungal aerosol obtained in the PSP.…”
Section: Fungal Waste-sorting Plant Exposure Dose (Fwsped)supporting
confidence: 53%
“…The most significant environmental factor influencing the viability of microorganisms is temperature. Higher temperature could promote the growth of fungi [41,42]. This is confirmed by the higher concentration levels of fungal aerosol obtained in the PSP.…”
Section: Fungal Waste-sorting Plant Exposure Dose (Fwsped)supporting
confidence: 53%
“…Spring was selected because it typically has the highest concentration of bioaerosols. The studies presenting seasonal fluctuations of bioaerosol concentrations, the size distribution of bacterial aerosols and their relationship with different meteorological factors [34,35] as well as our studies performed in the Upper Silesia Region indicate the highest concentration of airborne bacteria aerosols during spring [36][37][38]. In winter, extreme conditions such as low temperatures and the heaviest rainfall and snowfall of the year result in the decrease of bacteria levels.…”
Section: Sampling and Analysis Methodsmentioning
confidence: 70%
“…Our previous measurements showed that in the atmospheric air (especially in spring and summer seasons), there is an interplay of two opposing mechanisms, i.e., the rapid growth of bacterial particles and a relatively higher mortality of fine particles, which are normally isolated bacterial cells. This results in the observed seasonal size distribution, characterized by a low share of fine particles (< 3.3 μm) and a relatively large share of coarse particles (> 3.3 μm) (Brągoszewska et al 2017). Figure 3 shows that small particles, less than 3.3 μm, are more prevalent in indoor air after 5-6 h of work, which means that the bacteria were present in the indoor air mainly as single cells.…”
Section: Particle Size Distribution and Mass Median Aerodynamic Diamementioning
confidence: 91%
“…The size distribution of a bacterial aerosol is a powerful tool for understanding how building design, occupancy, and operation affect human exposure to airborne particles (Nazaroff and Cass 1989). Modeling the dynamics of the airborne bacteria depends upon the community structure of bacteria, the age of the spores, and differences in spore aggregation rates, as well as the type of particles they are associated with, such as mist or particulate matter (Brągoszewska et al 2017). Figure 2 shows an example of the mean size distribution of bacterial aerosols in the outdoor air during our research (late spring season).…”
Section: Particle Size Distribution and Mass Median Aerodynamic Diamementioning
confidence: 99%